2006
DOI: 10.2175/106143006x143939
|View full text |Cite
|
Sign up to set email alerts
|

Full‐Scale Class A Biosolids Production by Two‐Stage Continuous‐Batch Thermophilic Anaerobic Digestion at the Hyperion Treatment Plant, Los Angeles, California

Abstract: The City of Los Angeles Hyperion Treatment Plant (HTP) (California) converted its anaerobic digesters to thermophilic operation to produce Class A biosolids. Phase IV tests demonstrated compliance of a two‐stage, continuous‐batch process with Alternative 1 of U.S. Environmental Protection Agency 40 CFR Part 503 (U.S. EPA, 1993), which defines the time–temperature requirement for batch treatment (T ≥ 56.3°C at 16‐h holding). Fecal coliforms, Salmonella sp., viable helminth ova, and enteric viruses were not dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The continuous-batch process in Phase IV was the only process that met the time-temperature relationship of Alternative 1 (Iranpour et al, 2006b). As expected, fecal coliforms and pathogens were completely eliminated in the digesters and fecal coliform recurrence in post-digestion did not occur.…”
Section: Discussionsupporting
confidence: 54%
“…The continuous-batch process in Phase IV was the only process that met the time-temperature relationship of Alternative 1 (Iranpour et al, 2006b). As expected, fecal coliforms and pathogens were completely eliminated in the digesters and fecal coliform recurrence in post-digestion did not occur.…”
Section: Discussionsupporting
confidence: 54%
“…It is expected that fecal regrowth or contamination observed in phases I and II will be resolved: (a) once full conversion to thermophilic digestion has been completed and mesophilic biosolids are no longer produced; and (b) all biosolids transfer lines and the storage silos have been insulated and heat‐traced to prevent temperatures in the postdigestion train from dropping to values that could allow the regrowth of fecal coliforms. Results of phases III, IV, and V testing have been submitted for publication ( Iranpour and Cox, 2005 ; Iranpour et al, 2005c ).…”
Section: Future Directionsmentioning
confidence: 99%
“…These studies were similar to a wide variety of others during this period (e.g., Andrews and Pearson, 1965 ; Fair and Moore, 1934 ; McCarty, 1964 ; Pohland and Bloodgood, 1963 ), in being motivated, to a large degree, by the hope that the more rapid metabolism of thermophilic organisms would translate into advantages in digestion speed or operational efficiency, if process stability could be maintained. Recent interest in thermophilic‐anaerobic digestion at the HTP is driven by stricter regulations for removal of pathogens from wastes being digested for final use as a soil amendment ( Ahring et al, 2001 ; Ghosh, 1998 ; Iranpour and Cox, 2005 ; Iranpour et al, 2002 , 2004 , 2005a , b , and c ).…”
Section: Introductionmentioning
confidence: 99%
“…As discussed by Iranpour et al (2003b;2005b), full-scale testing indeed confirmed that fecal coliform recurrence did not occur after these modifications were implemented. Figure 3.…”
Section: Discussionmentioning
confidence: 75%